Badass making users awesome - Sierra, Kathy (O'Reilly Media, 2015)
The answers to what makes a sustainable bestseller aren't in the successful product. The answer lies is helping users become badass not just at using the product, but at whatever it is the product can help them do and be. And some of those answers are surprising, counterintuitive, but can be implemented by anyone at any stage in a product's development. Everything our users experience is part of that context, and even the smallest improvements can have a dramatic impact.